Effect of Flow Behavior on the Production of PVA/Dextrin Microspheres - Jawad Hadi, Nizar; Jabbar Braihi, Auda; Kareem Mohammed, Sara (International Journal of Engineering and Technology, 2018)
This work studies the production of microspheres from biopolymer towards using  as drug carrier and elucidation of the effect of flow behavior on the properties of microspheres. Poly(vinyl alcohol) PVA of 2, 2.5, 3 wt%  was mixed with 18% Dextrin using sonication process and then stirred for 20 h at 5°C. Different samples were taken after 4, 8, 12, 16, and 20 hr during stirring process for each concentration. Optical Microscopy, Zeta potential and AFM were used to check the size, shape, distribution, and stability of microspheres at rest. Dynamic viscosity and shear stress of the samples were tested under (0.1-50) s-1shear rates at 37oC in vivo condition by using con-plate viscometer. The result show that the microspheres were formed in spherical shape in sizes up to 150 micrometers and the increasing of PVA concentration lead to the increasing of wall microsphere thickness. The first concentration have incipient instability and moderate stability for the second and third concentrations. Also, the viscosity curve exhibited non-Newtonian flow and shear thinning behavior at 2, 2.5 and 3 wt% PVA/Dextrin emulsion. The microspheres deformed at 50 s-1 shear rate for the first concentration. The microspheres keep stable in the second and third concentration due to the gradually shear thinning effect. The stability of microspheres of third concentration was higher than others at rest and dynamic test. A good agreement occurs between viscosity behavior and the microspheres characteristics and stability.